The Value of Postconditioning in Plastic and Reconstructive Surgery: A Systematic Review - Weng, Weidong; Zhang, Feng; Lineaweaver, William C.; Gao, Weiyang; Yan, Hede (Journal of Reconstructive Microsurgery, 2016)
Background Ischemia-reperfusion (I/R) injury by abrupt restoration of circulation after prolonged ischemia has still been an unsolved problem in plastic and reconstructive surgery. The concept of postconditioning (post-con), which has been well described in cardiovascular surgery, has been recently introduced in plastic and reconstructive surgery. As an “after-injury strategy,” post-con may be a promising approach to reduce I/R injury and improve flap survival after ischemia.Methods A systematic review was performed by searching electronic databases of PubMed and web of science to identify all the studies regarding the application of the post-con technique in plastic and reconstructive surgery between 1950 and 2015. Inclusion criteria were English articles with clear reporting the post-con techniques and detailed outcomes.Results In total, 476 articles were identified and 18 studies reporting post-con in plastic and reconstructive surgery met the inclusion criteria in this review, including 11 studies of mechanical post-con, 3 studies of pharmacological post-con, 1 study of both mechanical and pharmacological post-con, and 3 studies of remote post-con. All these studies reported protective effects of any kind of post-con techniques in I/R injuries and could improve flap survivals.Conclusion In general, the strategy of post-con may effectively reduce I/R injury and improve the survival of flaps after ischemia in animal studies, yet no consensus regarding the exact technical details (intervention timing, cycles, intermittent duration, etc.) has been reached. Further studies aiming to explore its mechanisms as well as specific methodology are required before clinical application in plastic and reconstructive surgery.
Keywords: postconditioning; plastic and reconstructive surgery; ischemic and reperfusion injury; surgical flaps; mechanisms